Tom Clancy's Op-Center. Sting of the wasp - Rovin, Jeff; Clancy, Tom, 1947-2013; Pieczenik, Steve R (Clancy, Tom, 1947-2013. Tom Clancy's Op-center., 2019)
"After an intelligence failure at Op-Center results in a major terrorist attack, director Chase Williams radically transforms the agency into a ground-breaking new mobile strike force."--